Stalk-eyed flies carrying a driving X chromosome compensate by increasing fight intensity - Paczolt, Kimberly A.; Pritchard, Macy E.; Welsh, Gabrielle T.; Wilkinson, Gerald S.; Reinhardt, Josephine A. (Frontiers in Ethology, 2024)
Exaggerated ornaments provide opportunities for understanding how selection can operate at different levels to shape the evolution of a trait. While these features aid their bearer in attracting mates or fending off competitors, they can also be costly and influenced by the environment and genetic variation. Eyestalks of the stalk-eyed fly, Teleopsis dalmanni, are of interest because eyestalk length is the target of both intra-and intersexual selection and is also reduced by loci on a highlydiverged sex ratio X chromosome (X SR ), a meiotic driver accounting for up to 30% of wild X chromosomes. Male stalk-eyed flies fight to control access to females and over food using a combination of low intensity displays and high intensity physical fights. We staged, filmed and scored contests among eyespan-matched male pairs to evaluate whether X chromosome type impacts the behavior and outcome of aggressive interactions. While our results broadly match expectations from previous studies, we find that X SR males used more high intensity behaviors than males carrying a non-driving, standard X chromosome (X ST ), in particular when their eyestalks were of similar size or smaller than their opponents. Additionally, we find that when X SR males use high intensity behaviors they win more bouts than when they use low intensity behaviors. Taken together these results suggest that X SR impacts male aggressive behavior to compensate for the shorter eyestalks of X SR males, and may help to explain how this selfish chromosome is maintained.